Blow–Out Orbital Fracture Reconstructive Surgery Classical Technique - Ceballos, Ramon Navarro; Suarez, Jonathan Navarro (Journal of Ocular Diseases and Therapeutics, 2018)
Feminine, 42 years old. Car accident, 1 week after intensive therapy, presented dyplopie with severe orbital fracture. Besides right nasal bones fracture with internal canthal ligament section, enophtalmos and low ocular muscles herniaetion and haemathome into right maxilar sinus, Any calvary bone fracture.